Kingdom of the Netherlands-Curacao and Sint Maarten : Technical Assistance Report-Implementation of Risk-Based Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The CBvCSM is the sole supervisory authority for all regulated financial institutions operating locally and in the offshore (or international) sector, as well as the stock exchange in Curacao and St Maarten. The financial sector comprises different types of institutions, which include banks and non-bank institutions, insurance companies (both Life, and Non-life), securities intermediaries, asset management firms, investments institutions, fund administrators, management of pension funds, reinsurers, and trust companies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy